Physical activity of Mexican youth: a comparative analysis between public and private universities - García Rodríguez, Jaime; Fonseca Hernández, Carlos (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2012)
Physical activity appears in history from the moment when the human being comes in the face of the earth as a character inneed of movement, which has appeared since the beginning of mankind in various aspects such as mechanical motion, andsocial work. This has evolved directly in proportion to human development, reaching today to stand as a vital part of the training of individuals and as an indispensable means to achieve health, but there is also a bias in the practice of this activity and sport, which has created a cult of the body based on a postmodernism influenced by the mass media and standards of an alleged physical beauty sometimes unattainable human reality which has led to the presence of physical, biological, but equally psychological way, affecting self-esteem and self-image of young people and adolescents, which is in search of his identity. These kids today are influenced by a lifestyle dominated by modernity and technological advances, resulting in a sedentary lifestyle which adversely in every way and all areas, which coupled with institutional programs educational system and countless sports established deficiencies, leads to further complicate the situation, where you add harmful factors ranging from ignorance, inability and personal interests, which do not help us to build alternatives to start working. It is essential to establish an early and effective aimed at systematizing adequate physical activity based on scientific arguments and methods in line, we can provide various benefits given practice and help us stop the process of physical deterioration which the pace of modern life does not shed.